Réponses

2014-05-03T15:00:59+02:00
A= (√6+2)(√3-√2)
a = √18 -√12 +2√3 -2√2
a =√3²x2 - √2²x3 +2√3-2√2
a = 3√2 -2√3 +2√3-2√2
a = √2

B= (√5+√2)(√10-1)
b = √50 -√5 +√20 -√2
b = √5²x2 -√5 +√2²x5 -√2
b = 5√2 -√5 +2√5 -√2
b = 4√2 +√5

  • Utilisateur Brainly
2014-05-03T15:06:31+02:00
Développer et réduire :

A= (√6 + 2)(√3 - √2)
A= √18 - √12 + 2√3 - 2√2
A= 3√2 - 2√3 + 2√3- 2√2
A= √2

B= (√5 + √2)(√10 - 1)
B= √50 - √5 + √20 - √2
B= 5√2 - √5 + 2√5 - √2
B= 4√2 + √5

Si tu as des questions, n'hésite pas! =)